Brain stimulation methods for pain treatment - Kvašňák, Eugen; Rokyta, Richard (General physiology and biophysics, 2018)
Treatment of pain is one of the most important aims of medicine. Over the past several decades, invasive, semi-invasive and non-invasive brain stimulation methods have been tested and implemented for modulation of the pain. In this review, we bring an overview of those methods including stimulation of both deep brain structures utilizing invasive and semi-invasive techniques and the brain cortex stimulated by non-invasive transcranial magnetic and electrical techniques. Another potentially beneficial method that could modulate pain by stimulating the deep brain with interferential transcranial alternating current is discussed as well.
Keywords: Electric Stimulation Therapy; Pain Management; mozek; management bolesti; Humans; lidé; transkraniální magnetická stimulace; Brain; elektrostimulační terapie; Transcranial Magnetic Stimulation